Peran Guru dalam Pendidikan Kebersihan di Desa Teratai, Kecamatan Marisa, Kabupaten Pohuwato - Muh. Wahyuddin S. Adam; Lilin Abdjul; Eyn Hiola; Nur Anisa Nule; Septi Suhartati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Cleanliness is a fundamental aspect of life that plays an important role in maintaining the health of individuals and society. The concept of cleanliness covers various aspects, starting from personal cleanliness, the environment, to the cleanliness of the residence. Research shows that good hygiene can prevent the spread of disease, improve quality of life, and create a comfortable and productive environment. However, challenges in maintaining cleanliness include lack of public awareness, limited access to sanitation facilities, and poor waste management. Therefore, collaborative efforts are needed from individuals, communities and governments to increase awareness of the importance of cleanliness through education, health campaigns and the provision of adequate facilities. By maintaining cleanliness, it is hoped that a healthier, more prosperous and sustainable life will be created.